2015
DOI: 10.1128/jcm.01722-14
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine Leukocidin (PVL)-Positive Health Care-Associated Methicillin-Resistant Staphylococcus aureus Isolates Are Associated with Skin and Soft Tissue Infections and Colonized Mainly by Infective PVL-Encoding Bacteriophages

Abstract: Staphylococcus aureus, particularly methicillin-resistant S. aureus (MRSA), is a major human pathogen. MRSA can cause skin and soft tissue infections (SSTIs), as well as pneumonia, bacteremia, and sepsis (1). The majority of MRSA infections are caused by only a small number of clones. For example, the major clones in the United Kingdom are epidemic MRSA 15 (EMRSA-15) (clonal complex 22 [CC22] and sequence type 22 [ST22]) and EMRSA-16 (CC30 and ST36), whereas in Japan, Hungary, and the United States, the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 33 publications
9
53
0
4
Order By: Relevance
“…2c). PVL is a bicomponent pore-forming cytotoxin assembled by LukS-PV and LukF-PV and closely related to the development of S. aureus infection (Hu et al, 2015). Most MSSA strains and successful MRSA clones present high frequency of PVL carriage (Ruimy et al, 2008).…”
Section: Toxins Carriage By S Aureus Clone St121mentioning
confidence: 99%
“…2c). PVL is a bicomponent pore-forming cytotoxin assembled by LukS-PV and LukF-PV and closely related to the development of S. aureus infection (Hu et al, 2015). Most MSSA strains and successful MRSA clones present high frequency of PVL carriage (Ruimy et al, 2008).…”
Section: Toxins Carriage By S Aureus Clone St121mentioning
confidence: 99%
“…The risk of the prevalent PVL-positive healthcare-associated MRSA (HA-MRSA) strains is a serious concern that can result in the emergence of multidrug-resistant HA-MRSA isolates with increased virulence [13,14] . A study by Hu et al [14] reported the PVL positivity rate among MRSA strains to be 28.6%. In another study by van der Mee-Marquet et al [30] , this rate was determined to be 33.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Panton-Valentine leukocidin (PVL) toxin, which is an important virulence factor of S. aureus, may cause serious necrotizing infections with high mortality (56%-63%) in healthy and young individuals [12] . Therefore, epidemiological studies uncovering the clonal spread of S. aureus strains in the hospital and community settings are crucial [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Associations with osteomyelitis and pyomyositis are now strongly suggested [117][118][119][120][121][122][123]. The locus encoding PVL is inside related bacteriophages [124][125][126][127]128]. But the recent emergence of methicillin-resistant strains (MRSAs) producing this toxin may confer an increased morbid risk and necessitates careful therapeutic attitudes [129][130][131].…”
Section: Panton-valentine Leukocidin (Pvl)mentioning
confidence: 97%